Graphic Interface Implementation for Studying Magnetotransport Properties in Bilayers of Manganites Type Perovskite (2014)
In this work, a study of some magnetotransport properties of manganite bilayers of ferromagnetic/Antiferromagnetic (FM/AF) La2=3Ca1=3MnO3/ La1=3Ca2=3MnO3 is presented. This study was carries out using the Monte Carlo method combined with Drude and Kronig-